2001
DOI: 10.1128/iai.69.11.6718-6724.2001
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Vaccination with Pneumococcal Surface Protein A and Interleukin-12 Augments Antibody-Mediated Opsonization and Protective Immunity againstStreptococcus pneumoniaeInfection

Abstract: Streptococcus pneumoniae is a major pathogen in humans that enters the host primarily through the respiratory tract. Targeting mucosal surfaces directly may therefore be an optimal approach for vaccination to prevent bacterial colonization and invasive disease. We have previously demonstrated the effectiveness of interleukin-12 (IL-12) delivered intransally (i.n.) as an antiviral respiratory adjuvant. In this study, we examined the effects of i.n. IL-12 treatment on induction of protective humoral immunity aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
97
0
11

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(110 citation statements)
references
References 44 publications
1
97
0
11
Order By: Relevance
“…In addition, intranasal vaccination with PspA and IL-12 provided increased protection against nasopharyngeal carriage. The aforementioned results were obtained using a T-dependent pneumococcal protein antigen as the vaccine but, importantly, similar results have been observed using pneumococcal and meningococcal polysaccharide vaccines, given either as T-dependent conjugate vaccines, for example Prevnar ® , or as T-independent nonconjugated vaccines, such as Pneumovax ® [23][24][25]28,32]. In both cases, it was found that IL-12 treatment at the time of immunization induced significantly elevated levels of IgG2a and IgG3 anti-polysaccharide antibodies in serum, as well as IgA and IgG antibodies in the lung.…”
Section: For Reprint Orders Please Contact Reprints@expert-reviewscomsupporting
confidence: 65%
See 2 more Smart Citations
“…In addition, intranasal vaccination with PspA and IL-12 provided increased protection against nasopharyngeal carriage. The aforementioned results were obtained using a T-dependent pneumococcal protein antigen as the vaccine but, importantly, similar results have been observed using pneumococcal and meningococcal polysaccharide vaccines, given either as T-dependent conjugate vaccines, for example Prevnar ® , or as T-independent nonconjugated vaccines, such as Pneumovax ® [23][24][25]28,32]. In both cases, it was found that IL-12 treatment at the time of immunization induced significantly elevated levels of IgG2a and IgG3 anti-polysaccharide antibodies in serum, as well as IgA and IgG antibodies in the lung.…”
Section: For Reprint Orders Please Contact Reprints@expert-reviewscomsupporting
confidence: 65%
“…For example, upon transfer of sera to naive recipients and intranasal challenge with a lethal dose of S. pneumoniae, all mice that received normal mouse serum succumbed to infection within 5 days, and mice receiving serum from animals vaccinated with pneumococcal surface protein A (PspA) alone showed no significantly increased protection [31]. Strikingly, every mouse that received serum from animals treated with both PspA and IL-12 survived the infection.…”
Section: For Reprint Orders Please Contact Reprints@expert-reviewscommentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins are, generally, antigenically conserved across all serotypes and stimulate a T-cell-dependent immune response resulting in more robust immunological memory (28). Several pneumococcal surface proteins have been shown to be effective immunogens and can prevent sepsis, pneumonia, and carriage in animal models (1,2,5,6,23,26).…”
mentioning
confidence: 99%
“…24 In addition, co-administration of PspA antigen and IL-12 as a nasal adjuvant enhanced PspA-specific IgG and IgA responses, with increased protection from nasal carriage. 25 In addition, nasal immunization with chitosan–DNA nanoparticles that express PspA elicited protective immunity against nasal colonization by S. pneumoniae . 26 Furthermore, an antigen-delivery method has been developed that targets claudin-4, a major cell-adhesion molecule in tight junctions that is highly expressed on the epithelium of nasopharynx-associated lymphoid tissue.…”
Section: Development Of a Nanogel-based Nasal Vaccine Against Pneumoniamentioning
confidence: 99%